PENERAPAN METODE BERCERITA DENGAN BONEKA TANGAN DALAM MENINGKATKAN KETERAMPILAN MENYIMAK DONGENG SISWA KELAS II SD NEGERI 51 PEKANBARU - Wiwit Nurjannah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The background of this research is students who find it difficult to listen to learning. This study aims to determine the differences and increase in students' listening skills using the storytelling method with hand puppets. This research was conducted in class II of SD Negeri 51 Pekanbaru. Based on the results of the study, it was found that there were differences in the skills of listening to fairy tales between the experimental class and the control class. In the final test of the experimental class and the control class obtained = 5.7697 ≥  = 1.666, so there are significant differences. Increased skills in listening to fairy tales also occurred in the experimental class from an average of 74, 44 to 86, 94 in the final test and a gain of 0.38 which included in the medium category. So, there is a difference and an increase in the skill of listening to fairy tales grade II students of SD Negeri 51 Pekanbaru using the method of telling stories with hand puppets